Expedient and efficient one pot synthesis of trifluoroethyl ethers from metal free 2, 4, 6-tris-(2, 2, 2-trifluoro-ethoxy)-[1, 3, 5] triazene1. Issue 44 (16th May 2015) - Mangawa, Shrawan Kumar; Sharma, Chiranjeev; kumar Singh, Ashawani; Awasthi, Satish K.
<x xml:space="preserve">Abstract</x> An efficient synthesis of fluorinated alkyl and aryl ethers was achieved by the use of s-triazene derived fluorinated reagent 2, 4, 6-tris-(2, 2, 2-trifluoro-ethoxy)-[1, 3, 5] triazene (TriTFET).